Life and Forms. The sociological Meaning of a Metaphor - Fitzi, Gregor; Mele, Vincenzo; Magatti, Mauro (Simmel Studies, 2018)
Simmel’s work has often been interpreted as a succession of disparate phases of development following contradictory epistemological paradigms and intellectual stances. By analysing the ‘money or life metaphor’ Hans Blumenberg delivered the paradigmatic assessment for the consistency of Simmel’s philosophical work. The present paper critically extends this approach in order to understand the meaning of Simmel’s life and forms paradigm and shows that its preeminent theoretical contribution concerns sociological theory. From the analysis emerges that Simmel’s delivers a consistent alternative to Parson’s conception of functional differentiation in form of a theory of qualitative societal differentiation. In this frame, Simmel’s critical adoption and transformation of Marx’ theory of societal conflict allows for the foundation of an open-end theory of the development of modernity in the different domains of culture.